Some problems finding the volume of polyhedrons - Gotleras, M. (Psichologija, 1962)
Some problems finding the volume of polyhedrons are rather simple in their formulation and are usually solved by applying formulae of spherical trigonometry and, therefore, are not used in school practice. For example, such is a problem requiring finding the volume of a parallelepiped according to the length of its three edges coming from one top, and the size of flat angles at this top.The article draws out dependence between a diagonal of the inscribed rectangle (“diagonals of the inscribed rectangle are proportionate to sines of the rectangle angles opposite them”) and shows the application of this dependence in finding the volumes of polyhedrons.
Keywords: volume of polyhedrons and trigonometry